Implementación del método de transporte en la COOTRAMUSUN R.L - López Cantarero, Paola Ariana; Montoya Benavidez, Elieth Damaris; Osejo Bermúdez, Brenda Lucrecia; Zeledón, Gabriela del Rosario (Universidad y Ciencia, 2017)
Revista Universidad y Ciencia, UNAN-Managua Año 2013 Vol. 7 N° 11